1971
DOI: 10.1103/physrevlett.27.83
|View full text |Cite
|
Sign up to set email alerts
|

Radial Dependence of Trapped-Particle Instabilities

Abstract: The radial localization of trapped-particle instabilities is studied for a peaked diamagnetic-frequency profile and for a realistic profile. In the later case it is shown that modes can be excited only with a high radial wave number. The correspondingly reduced coefficient of turbulent diffusion is computed for the collisionless instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…This can be accomplished, for instance, with the use of a hypothetical reaction of N-O bond dissociation, as shown in Scheme 1. It is noteworthy that such a reaction can be considered to be a case of isodesmic reaction, [67][68][69] which has been shown 50,52,[70][71][72][73][74][75] to be a valuable tool in estimating the energies of various intramolecular interactions. To have a consistent scheme of N-O bond strength estimation, we used the O atom in its singlet state (calculations were done as restricted in order to avoid HOMO-LUMO mixing), which corresponds most adequately to oxygen atom electron configuration in the generally accepted model of N-oxide bonding, with three LPs and one empty orbital (donated by LP from the N atom in N-oxide).…”
Section: Resultsmentioning
confidence: 99%
“…This can be accomplished, for instance, with the use of a hypothetical reaction of N-O bond dissociation, as shown in Scheme 1. It is noteworthy that such a reaction can be considered to be a case of isodesmic reaction, [67][68][69] which has been shown 50,52,[70][71][72][73][74][75] to be a valuable tool in estimating the energies of various intramolecular interactions. To have a consistent scheme of N-O bond strength estimation, we used the O atom in its singlet state (calculations were done as restricted in order to avoid HOMO-LUMO mixing), which corresponds most adequately to oxygen atom electron configuration in the generally accepted model of N-oxide bonding, with three LPs and one empty orbital (donated by LP from the N atom in N-oxide).…”
Section: Resultsmentioning
confidence: 99%
“…( 78) exhibits only one turning point. By postulating appropriate boundary conditions at large r to provide a second turning point, Jablon, et al [86] and Ross and Horton [87] have obtained radially non-local modes using the familiar WKB method. However, as noted in Ref.…”
Section: Radial Analysis-idmentioning
confidence: 99%
“…Except for the acoustics, the apparatus was similar to one described elsewhere. 1 Measurements were made with frequencies between 1 and 10 kHz along isochores following two different procedures. The velocity of second sound in He II was measured for e = 1 -T/T\^ 2x 10" 5 between saturated vapor pressure (SVP) and the melting curve.…”
Section: (5)mentioning
confidence: 99%
“…1 ' 2 Recently, Jablon, Laval, and Pellat 1 have shown that this radial eigenvalue problem is very sensitive to the precise mathematical form of the density profile, a result that is somewhat puzzling from a physical point of view. In this Letter, we discuss the growth of trapped-particle modes from a rather different point of view than has been taken in the past, and we show that a very strong localization of the fluctuations (i.e., a very short radial correlation length) would be expected for virtually any smooth, monotonic density profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation